Characterisation of high frequency inductive power transfer receivers using pattern recognition on the transmit side waveforms - Arteaga,Saenz JM; Lan,L; Kwan,CH; Yates,DC; Mitcheson,PD (IEEE, 2020)
This paper demonstrates the characterisation of inductively coupled receivers for high frequency inductive power transfer (HF-IPT) systems using pattern recognition on the inverter waveforms at the transmit side. The impedance reflected by the candidate receivers to the transmit coil was estimated using a model programmed to associate the experimental drain-voltage waveforms of the inverter when it drives a receiver under test to those when driving known loads. The necessity of employing this technique is due to the difficulty of accurately measuring current and voltage across the coil given the parasitic effects of probing and the precise skewing required to measure an impedance, especially at high Q-factor. The proposed technique is convenient for characterising and comparing the impedance reflected by candidate receivers for a particular application where there is a choice to be made with respect to the rectifier topologies and semiconductor technologies. Experimental results, using a 13.56 MHz 100 W inductive power transfer system, were obtained for a full-wave Class D rectifier using silicon (Si) and silicon carbide (SiC) Schottky diodes, and two Class E rectifiers using SiC diodes.